The Miracle of Women Suporters’ Fanaticism in Indonesian Football - Iqbal Doewes, Rumi; Kunta Purnama, Sapta; N., Islahuzzaman; Manshuralhudlori, (International Journal of Psychosocial Rehabilitation, 2020)
Women supporters in Indonesia are growing rapidly. Ladies Curva Sud is one of the Indonesian women supporters, which is very fanatical. The presence of the women supporters group has positive impacts on Indonesian society. Study purpose was to determine the fanaticism of Indonesian women supporters. This research used a qualitative method with a survey approach. The study results are as follows: First, women supporters are always present at every game conducted by an Indonesian league club. Secondly, enjoying the work of the team they like is realized in the form of collecting his favorite jersey and knickknacks of his favorite team while at the same time helping the team’s finances, and they memorize the greatness of the club's songs supported. Third, getting closer to the club and their idol player. Fourth, women fanaticism was manifested in their daily lives, which makes the club a top priority. Fifth, turn on flares as their identity.